Pengembangan Media Pembelajaran Berbasis Video Model Addie di SMA Citra Nusa Cibinong Bogor - Azhar Alwahid; Agus Suryana (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
This study aims to develop a model of learning media development in Civics lessons in high school. This development research using the ADDIE model (analysis, design, development, implementation, and evaluation). The resulting product is a video-based learning media on Civics subjects at SMA Citra Nusa Cibinong. This media was developed through the stages of analysis, design, development, implementation, and evaluation. The media component developed is a learning video based on the main theme that is adjusted to the core competencies and basic competencies in the syllabus for Civics subjects. All of these learning videos are implemented through a project based learning learning system, with the following learning steps: Opening the lesson with a challenging question (start with the big question), Planning a project (design a plan for the project), Arranging an activity schedule (create a schedule), Supervise the course of the project (monitor the students and the progress of the project), Assessment of the resulting product (assess the outcome), Evaluation (evaluate the experience). At the end of the learning process, the Civics teacher and students reflect on the activities and results of the projects that have been carried out.